Coping Power : Parent Group Workbook, 8-Copy Set. - Wells, Karen (Treatments that work., 2008)
The Coping Power Program is designed for use with preadolescent and early adolescent aggressive children and their parents and is often delivered near the time of children's transition to middle school. Aggression is one of the most stable problem behaviors in childhood. If not dealt with effectively, it can lead to negative outcomes in adolescence such as drug and alcohol use, truancy and dropout, delinquency, and violence. This program has proven effective in helping to avoid these types of problems. The parent component of the program consists of 16 group meetings also held during the 5th a.